The best online shopping website using fuzzy TOPSIS approach / Nurul Suhada Aziz ...[et al.] - Aziz, Nurul Suhada; Mohd Noor, Nurhaifa Izzaty Azira; Md Faisal, Nur Amira Shahida; Sharidi, Nur Syafiqa (Unit Penerbitan UiTM Kelantan, 2021)
One of the common problems faced by customers before shopping online is choosing the best shopping website to shop online. This is because there are many cases that the goods received do not reach their expectations. Therefore, it is important for the customers to choose the right shopping website that can be trusted. This study implements fuzzy TOPSIS to rank the best online shopping website. Factors that influence customers' selection are the technology acceptance factor, website service quality and specific holdup cost. Decision-makers are asked to rank these factors by giving rank from very high (VH) to very low (VL) for criterion assessment weight, while for alternative assessment from very good (VG) to very poor (VP); very high and very good indicate the most influencing factor while very low and very poor indicate the least influencing factors. Each data ranking is transformed into matrix form to get a normalized decision matrix (NDM). After that, the weighted normalized decision matrix and the distance of each alternative from the worse condition and the best condition were calculated. Lastly, the closeness of coefficient of each alternative was obtained and all the alternatives were ranked. The performance and ranking were measured based one the value of the relative closeness.